A Method for Evaluating Usability Mechanisms in Software Systems - Santos, Bruna Almeida; Palmeira, Eduardo Gabriel Queiroz; Mendes, Fabiana Freitas; Sales, André Barros de (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Usability is an essential quality in software, as it allows straightforward and intuitive interactions between the user and the system. Consequently, software developers must prioritize addressing usability issues to ensure the system is easy to use. Thus, developing a usability evaluation method that also functions as a learning tool for students through hands-on evaluation practice could be a helpful resource. This document proposes a method for evaluating usability mechanisms in software systems. The method includes both an evaluation process and a questionnaire. These were validated through a case study, and their guiding procedures were applied to evaluate two serious digital games and a web application. Then, interviews with the software evaluators were conducted to gather insights into their perceptions of the method's effectiveness. Although there are some reservations about using case studies for evaluations, the results indicate that our evaluation method effectively identifies usability problems in software. In addition, it can serve as a valuable learning resource, as the evaluation process leads to discussions among the evaluators about the implementation of usability mechanisms in software, thereby enhancing their understanding of these concepts.